Efficient and Persistent Profile Matching in the Propinquity Mobile Social Networks - Shaik, Amanullah; Jyotsna, L N B (International Journal of Computer Sciences and Engineering, 2014)
Mobile social networks (MSNs) refer to the social networking for making new connections. In the MSNs personal preferences is an imperative service, where user can find matching users within the range. In the existing systems all services, generally all users can create specific profile and publish it into social networks to interconnect with the new people. It may contain some sensitive information also these types of sensitive users may not publish their profile into social networks as a public. A propinquity mobile social network refers to virtual interaction with the data (BLUETOOTH/WI-FI) interfaces on their smart phones. These social networks are more popular due to the recently growth of smart phone users. To reveal sensitive userï¿½s profile is most vulnerable in these devices. In these services conflicts with the userï¿½s privacy concerns about reveal their personal profiles to complete strangers before deciding to interact with them. In this paper takes this open challenge to overcome with the novel strategy. In this paper prior security work is focused on privacy to usersï¿½ profiles with using high efficient symmetric cryptographic primitives.